Weed flora and soil seedbanks in fields dominated by Imperata cylindrica in the moist savannah of West Africa - Chikoye, David; Ekeleme, F. (Wiley, 2001)
Imperata cylindrica (L.) Raeuschel is a dominant and infamous grass weed in the savannah of West Africa. Research to reduce the weed to non-damaging levels is a priority activity at many agricultural institutions. The successful development and implementation of long-term I. cylindrica management strategies depend on the ability to predict changes in weed composition after I. cylindrica has been controlled effectively. The weed flora and soil seedbank were assessed from 329 fields dominated by this species in the fringes of the humid forest (HFF), coastal/derived savannah (CDS) and in the southern Guinea savannah (SGS) in 1996 and 1997. The objectives of the study were to correlate species composition of the weed flora with that of the soil seedbank and to determine the effect of management factors and soil properties on the composition of the weed flora. Species richness in the weed flora and in the weed seedbank was higher in the SGS than in the CDS and HFF. Mean weed density per field was generally higher in the HFF (156 ± 25.0 weeds m–2) than in the CDS (108 ± 8.1 weeds m–2) and in the SGS (92 ± 6.3 weeds m–2). Weed composition varied with agroecological zone as well as with management factors and soil properties. Sørenson’s index of similarity was low (mean=0.20) in all zones, indicating poor similarity between the weed flora above-ground and the soil seedbank.